EFFECT OF TRIPHALA ON NOISE STRESS INDUCED ALTERATION IN GLUCOCORTICOID AND CARBOHYDRATE METABOLISM - LATHA .S; VENKATARAMANAN.R; SRIKUMAR.R; VIJAY KUMAR R (International Journal of Pharma and Bio Sciences, 2015)
Stress is a daily phenomenon faced by every living being and it is essential for learning. The body response to stress involves a fight and flight response in which biological changes, prepares the body for emergency action. The aim of the present study is to find out the fifteen days repeated noise, stress exposure induced alterations in the carbohydrate metabolism and its prevention by treatment with Triphala. Wistar strain male albino rats were used for this study. The result shown that the 15 days repeated noise stress (4hrs/day) increases the plasma cortisol level, adrenal body weight ratio, blood glucose, insulin, liver phosphorylase enzyme activity and decreases liver and muscle glycogen stores, the enzyme glycogen synthase activity. These alterations are prevented by treatment with Triphala during stress exposure. These results suggest that Triphala mixture possess the active compounds that have adoptogenic activity and play important role in maintenance of level of the cortisol and carbohydrate metabolism during stress.